Abbreviation of preoperative fasting and use of supplementation as an adjunct: integrative review (Research, Society and Development, 2023)
The objective was to identify the risks and benefits between abbreviation of fasting time and the use of preoperative supplementation. Methods: This is an integrative review, carried out with studies from the databases Scielo, Medline, Pubmed, Lilacs, Bdenf e Ibecs, between the period 2017 to 2022, totaling a final sample of 10 articles. Results: It was found that patients who performed the abbreviated fasting had several benefits, the main ones being the reduction of nausea and vomiting, greater comfort, reduction of hospital stay time, reduction of hospital expenses and less need for post-operative ICU, not being observed any complication related to the abbreviation technique. Conclusion: The abbreviation of fasting proved to be beneficial in all analyzed studies, bringing benefits in several aspects throughout the perioperative period for patients, not triggering any complications, however, it was observed the need to train professional teams to perform the technique properly.